Multifunctional DNA Nanomaterials for Biomedical Applications. (19th March 2015) - Tam, Dick Yan; Lo, Pik Kwan
Abstract : The rapidly emerging DNA nanotechnology began with pioneer Seeman's hypothesis that DNA not only can carry genetic information but also can be used as molecular organizer to create well-designed and controllable nanomaterials for applications in materials science, nanotechnology, and biology. DNA-based self-assembly represents a versatile system for nanoscale construction due to the well-characterized conformation of DNA and its predictability in the formation of base pairs. The structural features of nucleic acids form the basis of constructing a wide variety of DNA nanoarchitectures with well-defined shapes and sizes, in addition to controllable permeability and flexibility. More importantly, self-assembled DNA nanostructures can be easily functionalized to construct artificial functional systems with nanometer scale precision for multipurposes. Apparently scientists envision artificial DNA-based nanostructures as tool for drug loading and in vivo targeted delivery because of their abilities in selective encapsulation and stimuli-triggered release of cargo. Herein, we summarize the strategies of creating multidimensional self-assembled DNA nanoarchitectures and review studies investigating their stability, toxicity, delivery efficiency, loading, and control release of cargos in addition to their site-specific targeting and delivery of drug or cargo molecules to cellular systems.